Correction: Combined mechanistic and genetic programming approach to modeling pilot NBR production: influence of feed compositions on rubber Mooney viscosity. Issue 11 (4th February 2021) - He, Ge; Luo, Tao; Dang, Yagu; Zhou, Li; Dai, Yiyang; Ji, Xu
Abstract : Correction for 'Combined mechanistic and genetic programming approach to modeling pilot NBR production: influence of feed compositions on rubber Mooney viscosity' by Ge He et al., RSC Adv., 2021, 11, 817–829, DOI: ; 10.1039/D0RA07257E .